1934
DOI: 10.1172/jci100641
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Blood in Chronic Respiratory Diseases, With Special Reference to the Volume of the Blood 1

Abstract: The character of the changes in the blood in cases of chronic pulmonary diseases has not been settled. Although patients with respiratory disturbances often have the appearance of those with polycythemia, it is questionable whether there is an actual increase in the blood and cell volume. Some investigators believe that the blood in these cases shows a polycythemic picture, which they believe to be due to interference with the proper pulmonary exchange of oxygen, resulting in a low tension of oxygen in the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1951
1951
1976
1976

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Blood volume studies in chronic obstructive non-specific lung disease have produced conflicting results. Some workers have concluded that red cell volume is not consistently elevated in a quantitatively normal manner for the level of hypoxia (Lemon, 1929;Kaltreider, Hurtado, and Brooks, 1934;Freedman and Penington, 1963;Vanier, Dulfano, Wu, and Desforges, 1963;Murray, 1965;Ayvazian, Richardson, and Silber, 1969). This subnormal response has been attributed in turn to severe hypoxia, hypercapnia, iron deficiency, chronic infection, and gastrointestinal bleeding.…”
Section: Royal Infirmary Sheffield and Northern General Hospital Shmentioning
confidence: 99%
“…Blood volume studies in chronic obstructive non-specific lung disease have produced conflicting results. Some workers have concluded that red cell volume is not consistently elevated in a quantitatively normal manner for the level of hypoxia (Lemon, 1929;Kaltreider, Hurtado, and Brooks, 1934;Freedman and Penington, 1963;Vanier, Dulfano, Wu, and Desforges, 1963;Murray, 1965;Ayvazian, Richardson, and Silber, 1969). This subnormal response has been attributed in turn to severe hypoxia, hypercapnia, iron deficiency, chronic infection, and gastrointestinal bleeding.…”
Section: Royal Infirmary Sheffield and Northern General Hospital Shmentioning
confidence: 99%
“…[1][2][3][4][5][6] Hypoxia under almost all other conditions is associated with a secondary polycythemia. In natives of the Peruvian Andes, Hurtado and co-workers clearly demonstrated that prolonged exposure to high altitudes will produce an increase in hemoglobin and hematocrit proportional to the degree of hypoxia.7 Similarly, it has been observed that patients with arterial hypoxemia due to cyanotic heart disease8,9 and occasionally due to chronic pulmonary disease have secondary polycythemia.…”
mentioning
confidence: 99%
“…This could be due to an increase in total red cell volume being masked by an increase in plasma volume (29,33). However, the total red cell volume and the haemoglobin mass were often found to be less than expected (12, 19,33); a suboptimal haematologic response was shown despite normal erythrocyte life (7,12,29,33) and apparently adequate production of erythropoietin (6,7,23,33). Only in a group of ex-miners with chronic bronchitis and/or silicosis did a close correlation between arterial oxygen saturation and the haematologic data point to an adequate polycythaemic response (4).…”
mentioning
confidence: 99%